2008
DOI: 10.1002/bit.22033
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae for oil: Strain selection, induction of lipid synthesis and outdoor mass cultivation in a low‐cost photobioreactor

Abstract: Thirty microalgal strains were screened in the laboratory for their biomass productivity and lipid content. Four strains (two marine and two freshwater), selected because robust, highly productive and with a relatively high lipid content, were cultivated under nitrogen deprivation in 0.6-L bubbled tubes. Only the two marine microalgae accumulated lipid under such conditions. One of them, the eustigmatophyte Nannochloropsis sp. F&M-M24, which attained 60% lipid content after nitrogen starvation, was grown in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

84
1,423
13
60

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 2,484 publications
(1,580 citation statements)
references
References 33 publications
84
1,423
13
60
Order By: Relevance
“…Because of the low solubility here the oxygen is of most concern. A possibly inhibiting concentration (for some 2.5 L reactor with LED Warm-white 2000 µE/m 2 /s University Karlsruhe PSI 300 ml with LEDs [83] Labscale Plate-Reactor algae4120% air saturation, for others4200%) can occur already after 1 min in a tube without gas exchange. Aspect 5: Mixing and auxiliary energy Although volumetric mass transfer is more than 2 orders of magnitude lower in photo-bioprocesses than heterotrophic stirred tank reactors (lower biomass concentration, lower specific turnover rates) mixing is an important issue.…”
Section: Interactions Between Physiology and Reactor Designmentioning
confidence: 99%
“…Because of the low solubility here the oxygen is of most concern. A possibly inhibiting concentration (for some 2.5 L reactor with LED Warm-white 2000 µE/m 2 /s University Karlsruhe PSI 300 ml with LEDs [83] Labscale Plate-Reactor algae4120% air saturation, for others4200%) can occur already after 1 min in a tube without gas exchange. Aspect 5: Mixing and auxiliary energy Although volumetric mass transfer is more than 2 orders of magnitude lower in photo-bioprocesses than heterotrophic stirred tank reactors (lower biomass concentration, lower specific turnover rates) mixing is an important issue.…”
Section: Interactions Between Physiology and Reactor Designmentioning
confidence: 99%
“…For example, it has been observed that often under phosphorus limitation bacteria compete with algae for this nutrient‐depressing algal growth, while under nitrogen limitation the effect of bacteria on algal growth may be neutral or positive, due to a balance between nitrogen release through organic matter degradation and nitrogen immobilization, while in a medium with no nutrient limitation bacteria may stimulate algal growth by providing CO 2 (Brussard and Riegmann, 1998; Danger et al ., 2007; Amin et al ., 2012; Ramanan et al ., 2016). This different behaviour may play an important role during the starvation of algal cultures, a condition often applied to favour the accumulation of storage products (oil/carbohydrate) for biofuel production (Rodolfi et al ., 2009; Bondioli et al ., 2012; Yao et al ., 2012; Garnier et al ., 2016). Bacteria, besides inhibiting algal growth due to competition for nutrients, may also release harmful compounds, such as algicidal molecules or exoenzymes (Amin et al ., 2012; Natrah et al ., 2014; Cooper and Smith, 2015; Fuentes et al ., 2016; Ramanan et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This microalga is one of the few actually in the market, as it is widely used in aquaculture (Abiusi et al ., 2014; Tredici et al ., 2009; Tulli et al ., 2012; Muller‐Feuga, 2013). Tetraselmis also represents a possible feedstock for biofuel production (Rodolfi et al ., 2009; Bondioli et al ., 2012; Biondi et al ., 2016), cosmetic applications (Pertile et al ., 2010) and also food as the species Tetraselmis chuii has recently been approved as novel food in the EU (AECOSAN, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…These advantages include: (a) capability of producing oil during all year long and with superior efficiency, therefore the oil productivity of microalgae is greater compared to the most efficient crops; (b) producing in brackish water and on not arable land [41]; not affecting food supply or the use of soil for other purposes [2]; (c) possessing a fast growing potential and several species have 20-50% of oil content by weight of dry biomass [2]; (d) Regarding air quality, production of microalgae biomass can fix carbon dioxide [2]; (e) nutrients for its cultivation (nitrogen and phosphorous, mainly) can be obtained from sewage, therefore there is a possibility to assist the municipal wastewater treatment [19,20]; (f) growing algae do not require the use of herbicides or pesticides [42]; (g) algae can also produce valuable co-products, as proteins and biomass after oil extraction, that can be used as animal feed, medicines or fertilizers [3,10], or fermented to produce ethanol or methane [5]; (h) biochemical composition of algal biomass can be modulated by different growth conditions, so the oil yield can be significantly improved [43]; and (i) Capability of performing the photobiological production of "biohydrogen" [22][23][24][25]44].…”
Section: Environmental Impacts For Tranpostation Fuelsmentioning
confidence: 99%